Assessment of runoff and sediment outflow at different land slopes with varying rainfall intensity storms under simulated condition - NEMA, SOURABH; KUMAR, AKHILESH; SINHA, JITENDRA (Journal of Soil and Water Conservation, 2020)
This study demonstrates the runoff and sediment outflow variations at selected land slopes on varying rainfall intensity storms. The study was carried out using rainfall simulation system at 2.00 %, 4.00 % and 6.00 % land slopes with considering three rainfall intensity storms viz. 9.00 cm/h, 13.20 cm/h and 17.00 cm/h. The runoff distribution pattern was observed for different combinations of rainfall intensity and slope. It was observed that the runoff distribution pattern varied with change in land slope for a particular rainfall intensity storm. The hydrograph were plotted to compare peak rate of flow and the time base for different combinations. The study result indicated that the runoff volume was increased with increase in land slopes for every case, however the time taken by runoff to attain peak for particular rainfall intensity got reduced as land slope was increased from 2.00 % to 6.00 %. The sediment concentration and sediment yield was also shown a positive correlation with the increase in land slope as well as in rainfall intensity. The mathematical relationship to determine the sediment yield and sediment concentration has also been derived considering rainfall intensity and land slope factor.